El problema de los problemas en el perfil de la tesis de investigación jurídica - Casazola Ccama, Juan (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2022)
In this writing I focus on one of the factors that contributes to this reality, such as those contradictory positions about the approach to the research problem. The purpose is to note that the positivist tradition, with high degrees of conceptual and methodological purity criteria in legal research, has not allowed dialogue and changes in the epistemological position. I maintain that qualitative research is a fertile field to strengthen interactivity over one-sidedness, the experiential character among those who possess scientific knowledge; as well as social knowledge, popular knowledge, in the integral perspective of the ecology of knowledge, as the study of all existing sciences in the world.